English Language Teaching Strategies For Children With Dyslexia - Khairiah Zahara; Emeliya Sukma Dara Damanik (Universitas Islam Negeri Palopo, 2026)
This study investigates an overview of English language teacher learning strategies for children with dyslexia. This study presents a case study as a qualitative research of teachers in the ninth grade of SMP PAB 9 Medan. The sample consisted of 21 students (through purposive sampling. The criteria for teachers were that they taught how learning strategies were used in schools, and for the interview sample 3 Teachers. Multisensory and digital strategies were in accordance with the themes given by the researcher. This researcher used observation, documentation, and interviews. In this study, data collection from each instrument was as follows: document data collection through teacher learning strategies, and direct interview data collection at the location. The data analysis procedure for this study was followed by Lambert & Lambert, namely descriptive qualitative. Qualitative Descriptive Research, on the other hand, is entirely data-driven, with codes developed from data as the investigation progressed. The survey results show that most teachers already use a multisensory approach and technology to teach English to students with dyslexia. Around 75% of teachers often combine visual, auditory, and kinesthetic activities in their lessons, while 80% use digital tools such as E-Dyslexia, phonics apps, or text-to-speech programs. Teachers reported that these methods make students more active, motivated, and confident in learning. Overall, both the multisensory and technology-based approaches are seen as effective in helping dyslexic students improve their reading and writing skills.